1997
DOI: 10.1002/(sici)1098-2744(199708)19:4<273::aid-mc9>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic alterations in uterine leiomyomas and leiomyosarcomas by comparative genomic hybridization

Abstract: Uterine leiomyomas are the most prevalent tumor type in women of reproductive age and are the most common reason for hysterectomies. Although uterine leiomyomas are considered to be benign, they are a major public health concern for women. In contrast, leiomyosarcomas are rare but highly malignant uterine tumors. They may arise in uteri with preexisting leiomyomas and histologically sometimes resemble leiomyomas, thus causing controversy about whether leiomyosarcomas arise within leiomyomas. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Furthermore, when we performed the hierarchical cluster analysis, these tumors branched together even in smaller sub-clusters indicating that these histologically different entities cannot be distinguished based on copy number profiling. In concordance with the literature, leiomyosarcomas typically demonstrated the highest frequency of copy number alterations, 19,29,46 whereas leiomyomas showed a low number of copy number alterations with a few cases (20%) lacking any gains or losses. Interestingly, all cases of leiomyomas with bizarre nuclei and leiomyosarcomas showed a high number of copy number alterations involving nearly all chromosomes.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, when we performed the hierarchical cluster analysis, these tumors branched together even in smaller sub-clusters indicating that these histologically different entities cannot be distinguished based on copy number profiling. In concordance with the literature, leiomyosarcomas typically demonstrated the highest frequency of copy number alterations, 19,29,46 whereas leiomyomas showed a low number of copy number alterations with a few cases (20%) lacking any gains or losses. Interestingly, all cases of leiomyomas with bizarre nuclei and leiomyosarcomas showed a high number of copy number alterations involving nearly all chromosomes.…”
Section: Discussionsupporting
confidence: 87%
“…Gains/losses were identified in several regions, with the most common copy number gains in both UPS and LMS affecting 1p36. 33 The overall gains/losses are in accordance with studies that have applied cytogenetics and fluorescence in situ hybridization and showed extensive genetic alterations with recurrent numerical as well as structural aberrations, including losses of 1p36, 1q42-qter, 2p15-pter, 3p21-p23, 8p21-pter, 10q23-qter, 11q23-qter, 13q12-q13, 13q32-qter, and 18q11, and gains of 1q12-q31, in LMS. [30][31][32] CGH has also been applied to LMS 33 with the most frequent losses affecting 2p, 10q, 11q, and 13q, and the most common gains encompassing 1q, 5p, 8q, 17p, and Xp.…”
Section: Prognostic Correlationsmentioning
confidence: 99%
“…LMS are much more common in women than men, even for nonuterine locations. Until now, few cytogenetic or molecular data were available for LMS (Mandahl et al, 2000), and only a few series were analyzed by comparative genomic hybridization (CGH) (El-Rifai et al, 1998;Otano-Joos et al, 1998;Packenham et al, 1997;Parente et al, 1999). In this study, we analyzed a series of 27 LMS by immunohistochemistry and CGH.…”
Section: Discussionmentioning
confidence: 99%